A hidden hand in corporate lobbying. Issue 2 (6th August 2021) - Jiao, Anqi
Abstract: I investigate the role of institutional investors in firms' lobbying activities. Firms with greater lobbying institutional ownership lobby more. Using a novel dataset with lobbying information on congressional bills, I show that institutional investors support portfolio firms by lobbying together on same bills. Bills lobbied by institutional investors are more likely to become laws and the passage of such bills leads to greater abnormal returns. Additional evidence suggests that institutional investors protect firms' private political information by voting against shareholder proposals requesting additional lobbying disclosure. The findings have an important economic implication: financial institutions provide a helping hand in firms' external governance related to law and politics.